Sport and international relations : an emerging relationship - Levermore, Roger, 1971-; Budd, Adrian, 1961- (Sport in the global society., 2004)
Sport plays a highly significant role in the lives of millions the world over, and yet the impact of this global phenomenon on the subject of international relations hes been neglected. The contributors to this collection argue that sport remains both an underestimated and understudied aspect of international relations, and that the growth of its importance should be seen in the complex interdependencies and global systems of governance. The text examines:* how the expansion of professional sport, and the revenues generated by mass media's links with sport have transformed the internati.